2019
DOI: 10.1016/j.omtm.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Therapeutic Potential of Sulfamidase for the Treatment of Mucopolysaccharidosis IIIA

Abstract: Mucopolysaccharidosis type IIIA (MPS-IIIA) is a lysosomal storage disorder (LSD) caused by inherited defect of sulfamidase, a lysosomal sulfatase. MPS-IIIA is one of the most common and severe forms of LSDs with CNS involvement. Presently there is no cure. Here we have developed a new gene delivery approach for the treatment of MPS-IIIA based on the use of a modified version of sulfamidase expression cassette. This cassette encodes both a chimeric sulfamidase containing an alternative signal peptide (sp) to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“… 12 , 29 Recent data demonstrated that MPS-IIIA mice develop a strong age-dependent memory impairment in the contextual fear-conditioning test. 31 Indeed, untreated 9-month-old MPS-IIIA mice showed a severe memory deficit compared to WT mice, which, remarkably, was fully rescued by CLR01 treatment ( Figure 4 C). Taken together, our data showed that CLR01-mediated inhibition of amyloid formation in MPS-IIIA by CRL01 mice restores ALP function and reduces neuropathological signs significantly, thus indicating that amyloid deposition contributes to the neurodegenerative processes in a relevant model of neurodegenerative LSDs.…”
Section: Resultsmentioning
confidence: 87%
“… 12 , 29 Recent data demonstrated that MPS-IIIA mice develop a strong age-dependent memory impairment in the contextual fear-conditioning test. 31 Indeed, untreated 9-month-old MPS-IIIA mice showed a severe memory deficit compared to WT mice, which, remarkably, was fully rescued by CLR01 treatment ( Figure 4 C). Taken together, our data showed that CLR01-mediated inhibition of amyloid formation in MPS-IIIA by CRL01 mice restores ALP function and reduces neuropathological signs significantly, thus indicating that amyloid deposition contributes to the neurodegenerative processes in a relevant model of neurodegenerative LSDs.…”
Section: Resultsmentioning
confidence: 87%
“…1). We used only male mice, as differences in disease progression have been previously reported between female and male mice 23,24 . To dissociate early behavioural from late-occurring dementia-like behaviours, we focused on the analysis on 2-month-old MPS-IIIA and WT littermate mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal outcome of GT approaches in GLD as well as in other LSDs depends on the ability to boost enzyme bioavailability (production and secretion from donor cells) and cross-correction efficiency (enzyme uptake and delivery to lysosomes of affected cells), particularly in those tissues that are more refractory to correction due to their peculiar anatomy and physiology, such as CNS, PNS, bone, and heart. In line with studies performed in different LSD models (Gleitz et al, 2018;Sorrentino et al, 2019) we modified the GALC enzyme to increase its bioavailability. We show here that the IDSsp modification endows the GALC enzyme with increased secretion as compared to the native counterpart.…”
Section: Discussionmentioning
confidence: 69%
“…Studies performed in a murine model of MPS IIIA (a neurodegenerative LSD) have demonstrated the therapeutic efficacy of a chimeric sulphamidase engineered to increase its bioavailability by adding the signal peptide (sp) from the iduronate-2-sulphatase (IDS) and the BBB-binding domain (BD) from the Apolipoprotein B (ApoB) ( Sorrentino et al, 2013 , 2019 ). We took advantage of the same approach to generate LVs expressing chimeric GALC enzymes.…”
Section: Discussionmentioning
confidence: 99%